Carthamus tinctorius Suppresses LPS-Induced Anti-Inflammatory Responses by Inhibiting the MAPKs/NF-κB Signaling Pathway in HaCaT Cells - So-Yeon Kim; Minji Hong; Ponnuvel Deepa; Kandhasamy Sowndhararajan; Se Jin Park; SeonJu Park; Songmun Kim (MDPI AG, 2023)
This study aimed to elucidate the anti-inflammatory activity of C. tinctorius leaves by measuring inflammatory parameters such as nitric oxide (NO) production and mRNA expression of iNOS, interleukin-6 (IL-6), and IL-1β in lipopolysaccharide (LPS)-induced HaCaT cells. Further, the effect of C. tinctorius ethanol extract on the MAPKs/NF-κB signaling pathway was examined in HaCaT cells. The phytochemical profile of the ethanol extract of C. tinctorius leaves was determined using UPLC-QTOF-MS/MS. The results indicated that the ethanol extract of C. tinctorius effectively attenuated LPS-induced secretion of NO, IL-6, and IL-1β in HaCaT cells. Further, LPS-stimulated mRNA and protein expressions of iNOS were decreased by pre-treatment with C. tinctorius ethanol extract at the transcriptional level in HaCaT cells. Moreover, the ethanol extract of C. tinctorius suppressed NF-κB signaling in LPS-induced HaCaT cells. This suppression was mediated by MAPKs/NF-κB signaling, inhibiting the phosphorylation of p38 and p65 in HaCaT cells. However, there is no significant effect on the phosphorylation of JNK by the ethanol extract. The QTOF-MS/MS analysis revealed the identification of 27 components in the ethanol extract of C. tinctorius leaves. The data demonstrate that the ethanol extract of C. tinctorius leaves protects the LPS-induced HaCaT cells by inhibiting the expression of iNOS, IL-6, and IL-1β and suppressing the phosphorylation of the p38, p65, p-JNK via inactivation of MAPKs/NF-κB signaling pathway. These results demonstrate that C. tinctorius leaves may serve as a potential candidate to prevent inflammation-related diseases.